INVESTIGATION OF FUNGAL CONTAMINATION IN FRESH RAISIN JUICE IN MOSUL CITY AND ITS SUBURBS - Krmo, May Akram; Al_Rejaboo, Maha Akram Mohammad Ali (Journal of Medical Genetics and Clinical Biology, 2024)
Elected(40) a random sample of raisin juice from both sides of Mosul city (right and left) and its suburbs, which included the areas of Bashiqa, Al-Hamdaniya, Bartella, Al-Shekhan, Aqra and Dohuk, for the period from January 2023 to April 2024, to detect the extent of contamination of these samples with fungi and yeasts using the culture media Potato Dextrose Agar and Sabouraud Sucrose Agar. The results of the culture of the samples showed that there were fungi that grew on the two media and others that grew on one media. All isolates were diagnosed based on their morphological and biochemical characteristics and diagnosis using the planting medium. (121) fungal isolates of different species were obtained with a contamination rate of (100%) distributed as follows: The highest contamination rate for fungal species 33/121 (27.3%). Candida spp. and (27.3%)33/121 Apergillus spp., respectively, while I reached Contamination rate of raisin juice with Wickerhamomycesanomalus15/121(12.39%),Saccaromyces cervisiae14/121(11.57%), Rhotodorula spp.14/121(8.26%), and Penicillium ssp. and Exophiala dermatitidis (3.3%) each. Four fungal isolates wereFor each of them, followed by the following fungal species: Geotrichum spp. and Fusarium spp. and Epidermophytes floccosum by percentage pollution reached(0.82%) respectively but Pollution rate by Mushrooms(4/121(2.47% Cladosporiumoxysporu and (1.65%)2/121 Trichophyton mentagrophytonThe results of the study showed that (26)A sample of raisin juice was heavily contaminated with filamentous fungi and yeasts.By (65%)And it isR1, R3, R4, R5, R7, R9, R10, R11, R12, R14, R15, R16, R17, R19, R20, R21, R22, R26, R28, R29, R30, R35, R36, R38, R39, and R40. The other samples were contaminated with fungi at a low rate. And I ranto be sureDiagnosisfor fungal isolationUsing molecular methods to compare nitrogenous base sequences at the National Center for Biotechnology InformationNCBI using BLAST And it was recordedstrainnewAndCandida oleophilastrain MAYKAIY and sequenced as PP961930.1 in GenBankGlobal.